Extreme precipitation events in Novi Sad during the period 1961-2020 - Tošić, Ivana; da Silva, Antonio Samuel Alves; Filipović, Lazar; Putniković, Suzana; Stosic, Tatijana; Stosic, Borko; Đurđević , Vladimir (Geographica Pannonica, 2025)
Extreme precipitation events (EXPEs) were analyzed based on daily precipitation data from 1961 to 2020 in Novi Sad, Serbia. The temporal characteristics of the following EXPEs were investigated: Heavy precipitation days (R10mm), Very heavy precipitation days (R20mm), Highest 1-day precipitation amount (Rx1day), Highest 3-day precipitation amount (Rx3day), Highest 5-day precipitation amount (Rx5day), Very wet days (R95p), Extremely wet days (R99p), Precipitation fraction due to very wet days (R95pTot) and Precipitation fraction due to extremely wet days (R99pTot). The EXPEs were analyzed on an annual and seasonal basis and for two reference periods 1961-1990 and 1991-2020. Positive trends were found for both annual and seasonal values for all indices, except for R20mm and R99pTot in winter. A significant increase in Rx1day, Rx3day and Rx5day was observed in all seasons (except for Rx1day and Rx5day in winter) and on an annual basis. The high value of Rx1day (116.6 mm) was recorded in the summer of 2018 in Novi Sad, caused by convective precipitation that led to urban flooding. The possible influence of large-scale circulation patterns was investigated. A strong positive and negative influence of the East Atlantic pattern and the East Atlantic Western Russia pattern on the EXPEs was found. The results of this work support the growing evidence that the impact of extreme conditions is likely to become even stronger due to changes in their intensity and frequency.